Screening of inducers for laccase production by Lentinula edodes in liquid medium - Cavallazzi,José Renato P. (2005)
Laccases are enzymes involved in lignin degradation and are produced by various organisms. Due to their low substrate specificity their potential to be used in biotechnological applications has received attention. The addition of laccase inducers to the culture medium of microorganisms can enhance laccase production and facilitate its purification and utilization. The aim of this study was to investigate the effect of some compounds as laccase inducers in cultures of Lentinula edodes (shiitake). First, it was selected a culture medium suitable for laccase production by shiitake using two levels of N (2.6 and 26 mM) and seven levels of Cu (0, 50, 100, 150, 200, 250 and 300 µM). The medium with 2.6 mM N and 250 µM Cu was found to provide the highest laccase activity. To the selected medium it were added gallic acid (1 mM), catechol (1 mM), ammonium tartrate (55 µM), hydroxybenzoic acid (1 mM) and vanillin (1 mM). The two first compounds completely inhibited laccase activity and a 30 day time course experiment was carried out with the remaining compounds. Only cultures with ammonium tartrate exhibited laccase activity higher than control cultures, reaching 251 U/mL of extract after 30 days. A native-PAGE was performed and showed only one band, suggesting that no isozyme was produced.